Annealing effects on the microstructure and coercive field of two ferritic-martensitic Eurofer steels: A comparative study - Oliveira, V.B.; Sandim, M.J.R.; Stamopoulos, D.; Renzetti, R.A.; Santos, A.D.; Sandim, H.R.Z. (JOURNAL OF NUCLEAR MATERIALS, 2013)
Reduced-activation ferritic-martensitic steels are promising candidates for structural applications in future nuclear fusion power plants. Oxide dispersion strengthened ODS-Eurofer and Eurofer 97 steels were cold rolled to 80% reduction in thickness and annealed in vacuum for 1 h from 200 to 1350 degrees C to evaluate both their thermal stability and magnetic behavior. The microstructural changes were followed by magnetic measurements, in particular the corresponding variation of the coercive field (H-c), as a function of both annealing and tempering treatments. Results show that Y2O3 nanoparticles strongly affect the mechanical properties of ODS-Eurofer steel but leave their magnetic properties fairly unchanged when compared with Eurofer-97 steel. (C) 2012 Elsevier BM. All rights reserved.